2020
DOI: 10.31219/osf.io/7chpu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Government Capacity, Societal Trust or Party Preferences? What Accounts for the Variety of National Policy Responses to the COVID-19 Pandemic in Europe?

Abstract: European states responded to the rapid spread of the COVID-19 pandemic in 2020 with a variety of public policy measures. Governments across the continent acted more or less swiftly to close down schools, restrict arrival into their countries and travel within their territories, ban public meetings, impose local and national lockdowns, declare states of emergency and pass other emergency measures. Importantly, both the mix of policy tools as well as the speed with which they were enacted differed significantly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 17 publications
2
52
0
4
Order By: Relevance
“…A total of 175 countries were included in the study. Of these, 42 were located in Africa, 43 were in Asia, 5 were in Oceania, 47 were in Europe, 26 Worldwide, a maximum of 7 indicators were applied by governments. Another important factor was the total death rate in the studied countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 175 countries were included in the study. Of these, 42 were located in Africa, 43 were in Asia, 5 were in Oceania, 47 were in Europe, 26 Worldwide, a maximum of 7 indicators were applied by governments. Another important factor was the total death rate in the studied countries.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these countries' populations contain more elderly people, and most of the affected people were elderly; this could be another justification for such a high number of serious cases. 20,26 When comparing total SARS-CoV-2 infection rates among continents for the months of In addition, the increased global use of equipment to combat virus outbreaks caused food and supply shortages. The SARS-CoV-2 outbreak has had various impacts worldwide, especially in terms of disrupting factories and logistics operations.…”
Section: -1 7 -mentioning
confidence: 99%
“…European countries demonstrated a variety of national policy responses to the COVID-19 pandemic. Countries such as Romania, Bulgaria, and the Czech Republic, for example, introduced policy measures fairly quickly, with only 20 to 30 official cases of infection, whereas others, such as the Netherlands, Germany, and France, were very slow to react (Toshkov, Yesilkagit, and Carroll 2020). This variety may be attributed to both informal and formal institutional factors.…”
Section: The Institutional Dimensionmentioning
confidence: 99%
“…Using multivariate regression and survival analysis to model the speed with which school closures, national lockdowns, and states of emergency were announced in the EU member states, the UK, Switzerland, Iceland and Norway, Toshkov, Yesilkagit, and Carroll (2020) found that more centralized countries characterized by lower government effectiveness, freedom, and societal trust, yet with separate ministries of health and health ministers with a medical background, acted with greater speed and more decisively. One mechanism, recorded in east European countries, may have been increased awareness of limited capabilities regarding the handling of a serious health crisis, and the derived choice to act rapidly and aggressively (Capano et al 2020).…”
Section: The Institutional Dimensionmentioning
confidence: 99%
See 1 more Smart Citation